2022
DOI: 10.2478/aoas-2021-0044
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate supplementation at two forage levels in dairy cows feeding: milk production and composition, fatty acid profiles, blood metabolites, ruminal fermentation, and hydrogen sink

Abstract: Nitrate may reduce the ruminal methane emission by competing methanogenesis to achieve more hydrogen. For this purpose, twenty Holstein lactating cows were examined using a 2×2 factorial design in 4 groups for 60 days with two forage levels (40% and 60%) and supplemental nitrate 0% (F40 and F60) and 3.5% (F40N and F60N) of diet dry matter (DM). Then, the effect of nitrate and forage levels on cow performance, ruminal fermentation, methane emission, and metabolic hydrogen sink were evaluated. The nitrate supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 52 publications
2
3
0
Order By: Relevance
“…In addition to ammonium, changing the VFA profile can indicate changes in rumen fermentation and microbial activity. Similar to our results, an increase in acetate and a decrease in propionate by the nitrate supplementation have been preivusly reported by Hulshof et al (2012), Veneman et al (2015), Zhao et al (2015) and Sharifi et al (2021). Nonetheless, increasing the acetate and reducing the propionate may only illustrate the increase in accumulated hydrogen, not the change in methane production.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition to ammonium, changing the VFA profile can indicate changes in rumen fermentation and microbial activity. Similar to our results, an increase in acetate and a decrease in propionate by the nitrate supplementation have been preivusly reported by Hulshof et al (2012), Veneman et al (2015), Zhao et al (2015) and Sharifi et al (2021). Nonetheless, increasing the acetate and reducing the propionate may only illustrate the increase in accumulated hydrogen, not the change in methane production.…”
Section: Discussionsupporting
confidence: 92%
“…A disruption in NADH oxidation and subsequent reduction in NAD + concentrations have been shown to inhibit microbial fermentation (Hegarty and Gerdes, 1999). Conversely, the reduction in methane production could reduce energy lost through methanogenesis (Latham et al, 2016;Chen et al, 2019;Sharifi et al, 2021). Various studies have investigated the potential of unsaturated fatty acids, nitrate, sulphate, and fumarate as electron acceptors for the methane production reduction in livestock (Zeitz et al, 2013;Latham et al, 2016;Li et al, 2018).…”
Section: Graphical Abstractmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitrates and NO 2 − are alternative [H] sinks that divert H 2 away from methanogenesis and biohydrogenation, which would explain lower SFA in the present study; however, we are still lacking enough studies validating this hypothesis because of low H 2 dissipation at the expense of ruminal biohydrogenation (Yang et al, 2019). Indeed, similar to our results, Sharifi et al (2021) observed no effects of NO 3 − supplementation to dairy cows on 18:0 proportion, as indicative of biohydrogenation in the rumen. According to Lourenço et al (2010), biohydrogenation could be affected indirectly when other ruminal activities are changed (i.e., CH 4 inhibition), because FA metabolism is strictly dependent on the microbial species that are involved in multiple metabolic processes along with H 2 metabolism.…”
Section: Milk Fatty Acid Profilesupporting
confidence: 82%
“…The agricultural sector contributes to this problem by adding nitrogen to surface waters and the atmosphere (Pavlidis and Tsihrintzis, 2018;Sharifi et al, 2022). A ruminant production system should be ABSTRACT.…”
Section: Introductionmentioning
confidence: 99%